The Influence of Total Quality Management, Product Innovation and Process Innovation on the Performance of Recycling-Based SMEs in Sleman Regency - Rafida, Jasmine; Kusmantini, Titik; Sabihaini, Sabihaini (UPN Veteran Yogyakarta, 2024)
TQM has been proposed as a global advanced strategy to achieve quality goods and services that result in superior operational performance of SMEs. This study aims at the effect of TQM on product innovation, process innovation, and operational performance of SMEs and examines the effect of product innovation and process innovation on SME performance. Tests were also conducted to examine the influence of product innovation mediation variables and innovation processes on the relationship between TQM and SME operational performance. The study approach was carried out by collecting data through questionnaires through surveys. The respondents in this research were recycling-based SMEs in Sleman Regency, totaling 80 SMEs. The data analysis technique uses Partial Least Square (PLS). The results of this study indicate that TQM has a positive and significant effect on product innovation, process innovation, and operational performance of SMEs and product innovation and process innovation also has a positive and significant effect on SME performance. In addition, product innovation and process innovation positively and significantly mediate the relationship between TQM and SME operations. The results of this study have a theoretical contribution for future researchers and a practical contribution for business people, especially SMEs in order to continue to improve their operational performance.